ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS TENAGA KERJA WANITA DAN KOTRIBUSI PENDAPATAN (Studi Kasus Pada Usaha Belah Pinang Di Desa Paya Rangkuluh Kecamatan Kuta Blang Kabupaten Bireuen) - Meli Orlian; Ratna Ratna (Jurnal Ekonomi Pertanian Unimal, 2020)
The purpose of this study is to look at the factors that influence the productivity of female labor and income contribution (case study in Pinang split business in Payarangkuluh village, KutaBlang District, Bireuen Regency). The data used in this study are primary data obtained from 80 respondents. Data analysis method used is multiple linear regression. The results showed that the wages and total household income have a positive effect on the productivity of female labor, then age and level of education have a negative effect on the productivity of female labor, while together the variables of wages, age, level of education and total household income affected positively on the productivity of female labor in the village of Payarangkuluh Kuta Blang District Bireuen Regency.